2012
DOI: 10.1007/s00330-011-2372-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of arterial hypervascularity of hepatocellular carcinoma: comparison of contrast-enhanced US and gadoxetate disodium-enhanced MR imaging

Abstract: • Arterial hypervascularity is an important feature determining treatment options in hepatocellular carcinoma. • It can be assessed by contrast-enhanced (CE) ultrasound or magnetic resonance (MR) imaging. • CE ultrasound was more accurate than Gd-EOB-DTPA MRI in assessing intratumoral vascularity. • Hypovascular hepatic nodules should be further investigated using CE ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 32 publications
1
47
2
2
Order By: Relevance
“…From this standpoint, contrast-enhanced US may be the ideal modality as compared with CT and MRI [15,16] because continuous real-time observation of hemodynamic changes in an ablated lesion is possible and microbubbles are pure intravascular tracers that remain in the blood pool [17]. Moreover, contrast-enhanced US can be performed immediately after the IRE procedure without difficulty.…”
Section: Discussionmentioning
confidence: 98%
“…From this standpoint, contrast-enhanced US may be the ideal modality as compared with CT and MRI [15,16] because continuous real-time observation of hemodynamic changes in an ablated lesion is possible and microbubbles are pure intravascular tracers that remain in the blood pool [17]. Moreover, contrast-enhanced US can be performed immediately after the IRE procedure without difficulty.…”
Section: Discussionmentioning
confidence: 98%
“…It has actually become common to encounter cases where hypervascular HCC or nodule-in-nodule HCC that is undetectable by MDCT is detected in a routine screening by EOB-MRI because of early enhancement in the arterial phase or clear hypointensity in the hepatobiliary phase [11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103]. Furthermore, studies comparing the diagnostic performance of EOB-MRI and MDCT for hypervascular HCC have shown that EOB-MRI is superior or, at the very l...…”
Section: Diagnostic Algorithmmentioning
confidence: 99%
“…In addition, several authors have reported that CEUS is a better tool depicting arterial hypervascularity in HCC than CT or MRI. Bolondi et al [28] found that CEUS (61%) had a higher detection rate for early arterial enhancement than CT (49%) for lesions of ≤2 cm, and Sugimoto et al [29] reported that the diagnostic accuracies of average areas under the ROC curve were significantly greater for CEUS (average AUC 0.94, 95% CI 0.88-1.00) than for gadoxetate disodium-enhanced MRI (average AUC 0.84, 95% CI 0.74-0.93, p = 0.0014).…”
Section: Discussionmentioning
confidence: 98%